The Local Stability of Solutions for a Nonlinear Equation. (16th April 2014) - Yan, Haibo; Yong, Ls
Abstract : The approach of Kruzkov's device of doubling the variables is applied to establish the local stability of strong solutions for a nonlinear partial differential equation in the space L 1 ( R ) by assuming that the initial value only lies in the space L 1 ( R ) ∩ L ∞ ( R ) .